Que dire de la montagne ? Arthur Young dans les Pyrénées (1787) - Jacques Raynaud (Anglophonia)
At the end of the XVIIIth century, travel literature was supposed to provide information about the places visited by the author/narrator. Consequently, description is an essential feature of those books. When travel writers came to places which had no equivalent in their home country, they had nothing to refer their readers to to give them an idea of what they were talking about. That is the problem Arthur Young had to face during his stay in the Pyrenees in 1787. Objective description was practically impossible. The only way to convey an idea of what high mountains are like is through emotion but Young is obviously reluctant to let his feelings show. At the time, outbursts of feeling were considered as improper in that type of literature